1998
DOI: 10.1007/s004310050842
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal body weight curves for infants below 1000 g birth weight receiving early enteral and parenteral nutrition

Abstract: Our body weight curves are more adequate to evaluate growth of preterm infants than older published reference values because they are based on infants treated according to current nutritional standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 17 publications
4
49
0
7
Order By: Relevance
“…Similar results have been reported with the introduction of early amino acids suggesting that this intervention alone may be responsible for the improvement in early growth. [26][27][28][29] It is possible that the stress on the ELBW neonate losing 16% of their BW and weight loss continuing for 7 days of life may be setting the stage for the increase morbidities seen in the pre-EMPC cohort. The tolerance of an earlier initiation of feeds among neonates on CPAP and less oxygen may be related to the fact that these are less stressful interventions for these very immature infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been reported with the introduction of early amino acids suggesting that this intervention alone may be responsible for the improvement in early growth. [26][27][28][29] It is possible that the stress on the ELBW neonate losing 16% of their BW and weight loss continuing for 7 days of life may be setting the stage for the increase morbidities seen in the pre-EMPC cohort. The tolerance of an earlier initiation of feeds among neonates on CPAP and less oxygen may be related to the fact that these are less stressful interventions for these very immature infants.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced growth velocity in the post-EMPC group likely relates to the early anabolic state achieved with use of early amino acids. 17,27,28,30 In addition, the decreased energy required for healing from barotrauma, volutrauma and oxidant injury with use of CPAP and decreased oxygen saturation ranges is likely contributing to the enhanced growth.…”
Section: Discussionmentioning
confidence: 99%
“…Weight curves have been reported by Dancis et al, 11 Brosius et al, 12 Gill et al, 13 Shaffer et al, 14 Wright et al, 15 Ehrenkranz et al, 16 Pauls et al 17 and Berry et al 18 Head circumference and LEN curves were reported by Wright et al, 15 Ehrenkranz et al 16 and Berry et al 18 Tables and curves of predicted weights, HCs and LENs for BWs from 501 to 1500 g can be generated at the National Institutes of Child Health and Human Development (NICHD) website. 19 The objective of this report was to provide predictive curves for the growth of subjects in the NICU.…”
Section: Introductionmentioning
confidence: 91%
“…Gill et al, 13 Shaffer et al, 14 Wright et al, 15 Ehrenkranz et al 16 and Pauls et al 17 reported weight gain in terms of g/kg/day, which is an exponential growth constant. Patel et al 22 investigated linear and exponential methods for calculating postnatal growth velocity for weight and reported that the exponential method was the most accurate.…”
Section: Predicted Weightmentioning
confidence: 99%
See 1 more Smart Citation